Impaired renal function and associated risk factors in newly diagnosed HIV-infected adults in Gulu Hospital, Northern Uganda - Odongo, Pancras; Wanyama, Ronald; Obol, James Henry; Apiyo, Paska; Byakika-Kibwika, Pauline (BMC nephrology, 2015)
Screening for renal diseases should be performed at the time of diagnosis of human immunodeficiency virus (HIV) infection. Despite the high prevalence of HIV/AIDS in Northern Uganda, little is known about the status of renal function and its correlates in the newly diagnosed HIV-infected individuals in this resource limited region. We aimed to determine the status of renal function and factors associated with impaired renal function in newly diagnosed HIV-infected adults in Northern Uganda. Methods: This was a seven month cross-sectional hospital-based study, involving newly diagnosed HIV-infected patients, 18 years and older. Patients with history of diabetes mellitus, hypertension and renal disease were excluded. Estimated glomerular filtration rate (eGFR) was calculated using Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formula (Table one). Factors associated with impaired renal function (eGFR < 60 ml/min/1.73 m2) were thus sought.
Keywords: Renal function; Kidney disease; HIV; Gulu; Northern Uganda